QUADTREE FRACTAL COMPRESSION FOR BRAIN MRI IMAGES - Mir, J.; Raja, G. (The Nucleus, 2012)
Significant attention has been given recently to medical image compression due to benefits in archival and transmission of medical images. This paper describes the Quadtree fractal scheme for compression of Brain MRI medical images by defining the Region of Interest (ROI). Set of contractive transformations are found by using Partitioned Iterated Function system (PIFS). Fixed value of contrast scaling factor is used to compute the modified error function in implemented method reducing the encoding time. Various simulations are conducted to test the performance of Quadtree fractal compression scheme using different brain MRI medical images. Results are compared with Uniform partitioning fractal compression technique. Simulation results show good quality near lossless images with high compression ratio and acceptable PSNR values well above 30dB.